(adsbygoogle = window.adsbygoogle || []).push({}); 1. The problem statement, all variables and given/known data

If a+b+c = 0, show that [itex](2a-b)^3 + (2b-c)^3 + (2c-a)^3 = 3(2a-b)(2b-c)(2c-a)[/tex]

2. Relevant equations

None that I really need to state.

3. The attempt at a solution

Well I've just messed around with it, grinding through the algebra, and nothing seems to work. I did however notice that the (2a-b), (2b-c) and (2c-a) terms add up to a+b+c, and in this case, 0. So let u=(2a-b), v= (2b-c) and w=(2c-a) so that the question can be simplified to: if u+v+w = 0, then show [itex]u^3 + v^3 + w^3 = 3uvw[/itex].

First I need verification if this change is correct, then hints on what I should do next =[

**Physics Forums | Science Articles, Homework Help, Discussion**

Join Physics Forums Today!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Homework Help: Prove Equality given a condition

**Physics Forums | Science Articles, Homework Help, Discussion**